(3TQcGA dG ChUjGA (B:s (3GdESdGe hGdGSJLGHI dJWdYGJ GdCef GdHTQj (B: (3EPG GSJHYO faj GdBNQ hGSJOYj TQjcG adfJUhQ MGdI GdYGde jheFP (B! /s - (3GdQaGYj, MGeO Hf CMeO,s 1940- ((3LOI, GdSYhOjI (B:s (3eDJeQ GdYGde GdESdGej,s, 2006)
(3GdESdGe hGdGSJLGHI dJWdYGJ GdCef GdHTQj, EPG GSJHYO faj GdBNQ hGSoJOYj TQjckG adfJUhQ MGdI GdYGde jheFP (B!.s
Keywords: (3GdESdGe hGdCef GdOhdjs; (3GdESdGe hGdSdGe GdYGdejs